Função social dos negócios jurídico-adminstrativos - Mady, Fernando Keutenedjian (2012)
This work aims to demonstrate the possibilities of applying the principle of the social function to administration legal transaction, with its specificities. Justified the need of his scientific study by the fact that, despite it is a constitutional principle implicit, doctrine not gave adequate treatment and ample in the administration legal transaction. The methodology used was to demonstrate and to identify its origin to establish their effects on other areas and their differences with other legal institutions, conceptualize it and at the end, pointing their possible applications in various administrative activities. Was approached with the view that law was executed the exposed in the beginning. This was related to institutes or overlapping as objective good faith, trust in the protection of legitimate public interest and particularly by the Administrator. In preparing this essay, pointed to possible functions to the principle of social function in the legal and administrative business: integrative, interpretive and inhibitory